Hidden violence: How COVID-19 school closures reduced the reporting of child maltreatment - Francisco Cabrera-Hernández; María Padilla-Romo (Latin American Economic Review, 2020)
This study examines how school closures during the COVID-19 pandemic affected the reporting of child maltreatment in Mexico City. We use a rich panel dataset on incident-level crime reports and victim characteristics and exploit the differential effects between school-age children and older individuals. While financial and mental distress due to the COVID-19 pandemic may result in additional cases of child maltreatment, synthetic control and difference-in-differences estimations document an average reduction in child maltreatment reports of 29% and 30%, respectively, with larger reductions among females and in higher-poverty municipalities. These results highlight the important role education professionals in school settings play in the early detection and reporting of domestic violence against school-age children.
Keywords: I29; I31; J12; 330; Child maltreatment; Domestic Violence; COVID-19; School closures